Management Adaptation as a Mediator of Travel Agency Compliance: The Role of Regulations and Service Quality for Pilgrims at PT Nur Haramain Mulia - Noer Aida Fitriani; Jeni Susyanti; Abdullah Syakur Novianto (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the effect of regulatory implementation and the quality of services provided to pilgrims on travel agencies’ compliance, with management adaptation as a mediating variable, at PT Nur Haramain Mulia Kraksaan Probolinggo. The study employs a quantitative approach using a survey method. Data were collected through the distribution of questionnaires to respondents associated with Umrah travel agencies and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS. The results indicate that regulatory implementation has a positive and significant effect on travel agency compliance, whereas the quality of pilgrim services does not have a direct significant effect on travel agency compliance. Regulatory implementation and service quality for pilgrims have a positive and significant effect on management adaptation. Management adaptation also has a positive and significant effect on travel agency compliance and mediates the influence of regulatory implementation and service quality for pilgrims on travel agency compliance. These findings indicate that travel agency compliance is not only influenced by regulations and service quality but is also determined by the organization’s ability to adapt its management practices to changes in the environment and the demands of pilgrim services.